Rubidium doped nano-hydroxyapatite with cytocompatibility and antibacterial. Issue 1 (2nd January 2021) - Liu, Yanjun; Tan, Yanni; Wu, Jiangsong
ABSTRACT: Hydroxyapatite (HAp) is a widely used biomaterial because it is the main inorganic component of human bone and teeth. Rubidium (Rb) is a vital trace metal element in human body, and has been reported to possess antibacterial ability and can promote osteoblasts proliferation and differentiation. In this work, nanoscale hydroxyapatite particles doped with different contents of Rb (Rb-nHAp) were successfully prepared by hydrothermal method. X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR) were used to characterize the structure and morphology of the synthesized Rb-nHAp. XRD and FT-IR results show that the powders were pure HAp with good crystal structure and no other phase or impurity. SEM and TEM observations indicate that Rb-nHAp powders exhibit a homogeneous rod-like morphology, which were 50 ~ 300 nm in size. The in vitro results show that 3% and 5% Rb-nHAp exhibited enhanced proliferation and differentiation to MG-63 cells than pure HAp at day 7 or longer. In vitro bacterial proliferation assay shows that Rb-nHAp powders exhibit higher inhibition against the both bacteria. In conclusion, doping Rb could simultaneously endow nano-hydroxyapatite (nHAp) with favorable cytocompatibility and antibacterial capacity. Rb-nHAp can be a promising material for biomedical applications.